IGFBP-1 and IGFBP-2 are associated with a decreased pulse-wave velocity in young, healthy adults - Pettersson-Pablo, Paul; Nilsson, Torbjörn K.; Breimer, Lars H.; Hurtig-Wennlöf, Anita (BMC cardiovascular disorders, 2021)
Background and aims In healthy, young adults we analyzed a panel of cardiovascular disease related proteins in plasma and compared them with the vascular health of the subjects. The aim was to identify proteins with a relationship to the early atherosclerotic process in healthy individuals. Methods We employed the proximity extension assay from OLINK proteomics to analyze 92 cardiovascular disease (CVD) related proteins on 833 subjects (men and women, ages 18–26). The women were further divided into an estrogen-using group and non-users. Protein expression was analyzed using principal component analysis (PCA). The following vascular examinations were performed: Pulse-wave velocity (PWV), augmentation index (AIX), carotid-intima media thickness (cIMT). Results Three principal components were obtained using PCA to analyze the protein expression. None of the obtained principal components correlated significantly with AIX or cIMT. One of the components, explaining 6% of the total variance of the data, was significantly correlated with PWV. Upon examination of the proteins with the highest factor loadings on this component independently in a multivariable model, adjusting for established CVD risk biomarkers, insulin-like growth factor-binding protein 1 (IGFBP-1) and insulin-like growth factor-binding protein 2 (IGFBP-2) were found to independently, negatively correlate with PWV. Among the established risk factors included in the multivariable model, age was significantly and adversely correlated with all vascular measurements. Conclusions In this population of healthy, young adults, groups of CVD related proteins correlate with PWV, but not AIX or cIMT. This group of proteins, of which IGFBP-1 and IGFBP-2 were independently, negatively correlated in a multivariable model with PWV, could have benificial effects on vascular stiffness. The robust association between age and PWV, AIX and cIMT provide insight into the impact of aging on the vasculature, which is detectable even in a population of young, healthy, non-smoking individuals of ages spanning only 8 years.